Law Enforcement Against Criminal Acts of Corruption in The Form of Abuse of Authority in Office Based on The Law on Eradication of Corruption Crimes - OP.Sunggu, Eben Patar; Marbun, Warasman; Hartanto (JILPR Journal Indonesia Law and Policy Review, 2024)
The concept of abuse of authority in the Government Administration law is seen by several legal experts as the same as the concept of abuse of authority because it is the absolute competence of the Administrative Court in the Corruption Eradication law. The research method used is Case Study Decision Number Case Study Decision Number 218 PK/PID.SUS/2019 and Decision Number 143 PK/PID.SUS/2019, where both decision cases involve criminal acts of corruption in the form of abuse of authority in office. Based on Law no. 31 of 1999 Jo Law no. 20 of 2021 concerning the Eradication of Corruption Crimes. The conclusion is that the application of sanctions against criminal acts of corruption in Decision Number 218 PK/Pid.Sus/2019 and Decision Number 143PK/Pid.Sus/2019, the panel of judges imposed imprisonment/imprisonment and fines, the imposition of fines as an implementation of the balance value can be applied as long as In certain circumstances, the perpetrator of a criminal act of corruption is not a recidivist, then as a balanced punishment, apart from imposing a fine, assets can also be confiscated, this is so that the imposition of the fine can be used as a lesson or legal perspective for the wider community, rather than just being sentenced to imprisonment/ prisons are indeed less effective, because in the implementation of confinement/imprisonment sentences there are still leniencies which do not actually have a deterrent effect on perpetrators of criminal acts.